HUBUNGAN PENDIDIKAN DAN SIKAP DENGAN KEBERHASILAN TOILET TRAINING - erni buston; Septiyanti Septiyanti (MNJ (Mahakam Nursing Journal), 2017)
Growth and development in childhood is a crucial period that affect later development, such as language skills, crearivity, social awareness and emotional (Soetjiningsih, 2003). According to Sigmund Freud cit Sunaryo (2004), in theory that child enters the toddler stage marked by anal satisfaction (kateksis) and dissaticfaction (antikateksis) atound the function of elimination. In a study published by the Journal of Pediatrics (2002) says more than 50 percent of American children aged over 36 month are not sucsessful toilet traning, it caused a lot of Urology reported that the failure og toilet training increases the risk of bladder problem. A recent study Johnson (2010), mentions an increased risk of urinary inkontensia in childern aged over 36 month.This study uses a quantitative research with descriptive design with cross sectional analytic. The sample in this study is the mother and child in early childhood education and early childhood Baitul Izzah Ababil Bengkulu city bumbering 81 people. The collection of data by using a questionnaire sheet. The data analysis was conducted quantitative univariate and bivariat using Chi Square.The result of this study, the no relation between eduction and the mother with the success of implementing toilet training in childern in early childhood Ababil Izzah Bengkulu City 2016 p:0,663), there is a realitionship attitude to the success of implementing Toilet Training on their childern in early childhood Ababil and Baitul Izzah Bengkulu city 2016 (p:0,016) no relitionship Physical Readiness to implement successful Toilet Traning in Childern in early childhood educarion and Baitul Izzah Bengkulu city in 2016 (p:0,001).Expected early childhood teaching team can implement Toilet Taning activities on childern in eraly childhood education dropped off to improve gross motor development of childern so tahat childern still do development Keywords: toilet training, child aged 3 years